Evaluasi penerapan sistem informasi akuntansi berbasis SAP dalam kualitas penyajian Laporan Keuangan pada PT Sinergi Gula Nusantara - Atik Mufida (Qualitative Research of Business and Social Sciences, 2025)
The study aimed to determine whether the SAP-based Accounting Information System can improve the quality of financial report presentation at the Djombang Baru Sugar Factory. This study employed a qualitative case study approach. The primary data were obtained through interviews and observations. The data analysis used is data triangulation, comprising data reduction, data presentation, and conclusion. The results of this study indicate that the accounting information system at PGDBU significantly contributes to the quality of financial reports in the process of preparation and presentation. This study also found that SAP can improve the quality of financial report presentation and provide a structured system allowing online data processing at the head office.